The influence of financial knowledge, financial attitude, personality, and locus of control on financial management behavior - Setiabudhi, Hatta; Suwono, Suwono; Latif, Elok Ainur; Yusti, Dwi Julmulmiwah (Jurnal Mantik, 2025)
Basically, the financial management behavior of MSMEs in Kroya Market is influenced by various factors such as financial knowledge, financial attitudes, personality, and locus of control. Based on this, the purpose of this study is to determine the effect of financial knowledge, financial attitudes, personality, and locus of control on financial management behavior of MSMEs in Kroya Market. This study uses a quantitative method. The target population of this study consists of MSMEs in Kroya Market. This study involved 78 respondents. This study used multiple regression analysis techniques. Data were collected by distributing questionnaires to MSME traders in Kroya Market and processed using SPSS 25 for Windows. Based on the results of the study obtained, financial knowledge, financial attitudes, personality, and locus of control have a significant effect on financial management behavior. The determinant test of the independent variables showed an influence of 41.5% on the dependent variable